2010
DOI: 10.1186/scrt29
|View full text |Cite
|
Sign up to set email alerts
|

Intracoronary delivery of bone-marrow-derived stem cells

Abstract: Ischemic heart disease is the single greatest killer of Americans and its complications are a major cause of congestive heart failure and ventricular arrhythmias while signifiicantly contributing to increased health care costs and reduced patient quality of life. Advances in medical therapy, although signifiicant over the past decade, are still inadequate in regards to targeting the prime underlying pathology, the irreversible loss of damaged or dead cardiomyocytes. Research into the use of cell transplantatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 45 publications
0
19
0
Order By: Relevance
“…In fact, the meager number of progenitor cells homing and integrating into the myocardial architecture after conventional procedures is not determined by inherent myocardial impedimenta [39], but by the lack of at least two irremissible factors: proper culture of optimal progenitor cells and most favorable host tissue environment. Consistently, the present study was designed to verify the capability of properly cultured progenitor cells to home in a favorable host tissue environment (healthy myocardium).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, the meager number of progenitor cells homing and integrating into the myocardial architecture after conventional procedures is not determined by inherent myocardial impedimenta [39], but by the lack of at least two irremissible factors: proper culture of optimal progenitor cells and most favorable host tissue environment. Consistently, the present study was designed to verify the capability of properly cultured progenitor cells to home in a favorable host tissue environment (healthy myocardium).…”
Section: Discussionmentioning
confidence: 99%
“…Intracoronary infusion is another option to deliver cells into the myocardial region of injury. While this approach can minimize cell leakage and may limit their systemic diffusion, injected cells may not be retained well (16) and can cause acute myocardial ischemia and myocardial microinfarction (143). Cells may be delivered via a homing system, which enables endogenous or exogenous cells to migrate to a specific region.…”
Section: Cell Delivery and Survivalmentioning
confidence: 99%
“…Results obtained in pre-clinical animal models showed that this minimally invasive approach results in a significant percentage of injected cells being sequestered in lungs, liver or spleen, due to blood flow [33]. On the other hand, intracoronary or retrograde coronary sinus infusion of the cells are mainly performed after acute myocardial infarction using an angioplasty balloon and high pressure to deliver cells to heart muscle [34]. The coronary route was proven to be free of stem cell systemic delivery, while a limited number of cells could be found in the infarcted area [35].…”
Section: A) Direct Injectionmentioning
confidence: 99%